2012
DOI: 10.3174/ajnr.a3242
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Transient Reduced Diffusion in the Ipsilateral Striatum and Thalamus

Abstract: BACKGROUND AND PURPOSE:Restriction of diffusion has been reported in the early phase of secondary neuronal degeneration, such as Wallerian degeneration. The purpose of this study was to investigate postoperative transient reduced diffusion in the ipsilateral striatum and thalamus as a remote effect of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
1
3
0
1
Order By: Relevance
“…Such late occurrence of restricted diffusion in the striatum suggests secondary neurodegeneration (i.e., Wallerian degeneration) due to the widespread frontostriatal disconnection and has been reported to occur in a proportion of patients with resective-type frontal surgery. 9 The restricted diffusion was transient, reaching their peaks around 2 to 3 weeks after the surgery 9 as in our patients. However, similar findings have not yet been reported in patients who underwent frontal disconnection surgery.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Such late occurrence of restricted diffusion in the striatum suggests secondary neurodegeneration (i.e., Wallerian degeneration) due to the widespread frontostriatal disconnection and has been reported to occur in a proportion of patients with resective-type frontal surgery. 9 The restricted diffusion was transient, reaching their peaks around 2 to 3 weeks after the surgery 9 as in our patients. However, similar findings have not yet been reported in patients who underwent frontal disconnection surgery.…”
Section: Discussionsupporting
confidence: 67%
“…The striatal signal abnormalizes should not be confused with perioperative ischemic stroke. 9 They may pass unnoticed due to the lack of obvious neurological symptoms likely because the procedure is performed in patients with a vast frontal lesion or hypometabolism. The benign postoperative course despite the striatal degeneration supports the use of this surgical procedure in otherwise inoperable patients with broad frontal epileptogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Brodtmann et al [ 9 ] suggested that thalamic atrophy could be observed as early as 3 h after the onset of symptoms. In a population of 125 patients who had surgery for resection of a cortical lesion, Kamiya et al [ 28 ] observed transient diffusion restriction of the ipsilateral striatum and thalamus as early as 7 days after the intervention followed by atrophy of these structures; the extension of the anomalies being correlated with the extension of the resection. This indicates the presence of early morphological alterations of the interconnected structures within the striato-thalamo-cortical network ipsilateral to MCA stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Injuries to the corticostriatal pathways caused by hemorrhage or surgery involving the external capsule may induce transneuronal degeneration of the striatum [ 1 ]. It is convenient to know this uncommon entity because it mimics an acute ischemic lesion from another cause and should not be mistaken [ 2 ].…”
mentioning
confidence: 99%
“…Las lesiones de las vías corticoestriadas producidas por hemorragias o cirugías que afectan a la cápsula externa pueden inducir una degeneración transneuronal del cuerpo estriado [ 1 ]. Es conveniente conocer esta entidad infrecuente, porque simula una lesión isquémica aguda por otra causa y no debe confundirse [ 2 ].…”
unclassified